Knowledge and Practice in Household Waste Management - Widiyanto, Agnes Fitria; Suratman, Suratman; Alifah, Nisrina; Murniati, Tri; Pratiwi, Oktafiani Catur (UI Scholars Hub, 2019)
Declining environmental quality is one of population caused by household consumption behavior. Some of the highest contaminant contributions are domestic waste, waste, and company waste. Waste contamination will lead to dead fish, decreased water quality and disease transmission. Community approach can be done to solve the waste problem, especially at the household level. This study uses quantitative methods to analyze the effect of intervention and waste management training on changes in household waste management knowledge and practices. This type of research uses quasi experiment with one group of pre and post test design. The results showed that there was an increase of knowledge about waste management after being given intervention by the researcher because the p value ≤ 0,05. The results also show that there is an increasing practice on waste management after being given intervention by researchers because the p value ≤ 0.05. Based on the research results, it can be concluded that the provision of intervention is effective for improving knowledge and practice in the household waste management.